KESTABILAN MODEL MANGSA PEMANGSA DENGAN PEMANENAN THRESHOLD PADA MANGSA DAN ADANYA RACUN - , Saiful Marom; , Prof. Dr. Widodo, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The dynamics of a predator prey model with threshold harvesting on the prey and the presence of toxicity is studied in this thesis. Models is divided two problem are ecosystem with the absent of toxicity and ecosystem with the presence of toxicity. There are eight of equilibrium point. Then, all models are discussed about boundedness of solution, equilibrium point, the type of equilibrium point, and characteristic stability of equilibrium point.